Educommunication and organizational communication: a universe of possibilities and connections. - Rigo, Larissa Bortoluzzi; Gehlen, Ivana de Jesus; Tavares, Marcelo de Barros; Fortaleza, Keynayanna Késsia Costa (Organicom, 2017)
The article proposes a reflection about the convergences between educommunication (Soares, 2009) and organizational communication (Kunsch, 2016), by the perspective of information culture (Jenkins, 2006; Shirky, 2011). The theoretical focus considers organizational environments as spaces of interaction, construction and dispute of senses (Baldisssera, 2008), in a context distinguished by participatory culture, in spaces of non-formal education (Peruzzo, 2008). Finally, the connection across the concepts related to educommunication reveals new possibilities in the area of communication in organizational environments.